Pengaruh Kepemimpinan Transformasional, Budaya Perusahaan dan Kompensasi Terhadap Kinerja Karyawan PDAM Tirta Dharma Kota Salatiga - Riski Aryo Nugroho; Ari Pradhanawati; Rodhiyah Rodhiyah (Universitas Diponegoro, 2016)
The purpose of this research is to determine the influence of transformational leadership, corporate culture and compensation on the performance of the employees of PDAM Tirta Dharma Salatiga.This type of research is explanatory research. The population in this study is the employees of PDAM Tirta Dharma Salatiga with the total of 138 employees which is sampled 58 employees. Data were collected through interviews, questionnaires, and literature study. It uses Likert Scale for the measurement scale. For the method, it uses proportionate random sampling. For analyzing data, it uses simple linear regression and multiple linear regression to test the hypothesis using the t test and F test in SPSS 18.0. The results show that the transformational leadership has a positive influence on employee performance. Corporate culture on employee performance affect positive. Compensation to employee performance have positive effect. Together variable transformational leadership, corporate culture and compensation have positive influence on employee performance. The conclusion is that the transformational leadership, corporate culture, and compensation which are applied have been good and satisfactory. This research suggestions are the leaders should be more active in praising to the all subordinates every, employee should pay more respect of the co-workers opinions, and giving better and various compensation.